2013
DOI: 10.1002/jgrd.50125
|View full text |Cite
|
Sign up to set email alerts
|

On the lack of stratospheric dynamical variability in low‐top versions of the CMIP5 models

Abstract: [1] We describe the main differences in simulations of stratospheric climate and variability by models within the fifth Coupled Model Intercomparison Project (CMIP5) that have a model top above the stratopause and relatively fine stratospheric vertical resolution (high-top), and those that have a model top below the stratopause (low-top). Although the simulation of mean stratospheric climate by the two model ensembles is similar, the low-top model ensemble has very weak stratospheric variability on daily and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
309
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(340 citation statements)
references
References 48 publications
30
309
1
Order By: Relevance
“…There is a current interest from the NWP community to validate model specifications at stratospheric altitudes using independent observations [e.g., Randel et al, 2004;Charlton-Perez et al, 2013]. This includes the analysis of potential satellite radiance measurement biases, the consideration of additional high-resolution measurements (gravity waves and 10.1002/2014JD021632 momentum flux) that are currently not resolved in the model runs, and validation of currently employed gravity wave model parameterization schemes [Charlton-Perez et al, 2013].…”
Section: 1002/2014jd021632mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a current interest from the NWP community to validate model specifications at stratospheric altitudes using independent observations [e.g., Randel et al, 2004;Charlton-Perez et al, 2013]. This includes the analysis of potential satellite radiance measurement biases, the consideration of additional high-resolution measurements (gravity waves and 10.1002/2014JD021632 momentum flux) that are currently not resolved in the model runs, and validation of currently employed gravity wave model parameterization schemes [Charlton-Perez et al, 2013].…”
Section: 1002/2014jd021632mentioning
confidence: 99%
“…One example is the influence of the onset and duration of Sudden Stratospheric Warmings (SSWs) on the latitude of the tropospheric jet stream, as this has a strong impact on near-term weather forecasting [Gerber et al, 2009]. Weather and climate forecasters are moving toward a more comprehensive representation of the atmosphere, in order to capture the stratospheric-tropospheric interactions [Charlton-Perez et al, 2013]. The development toward such circulation models is facilitated by the increase in computational resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that, with high-top model, the common cold bias of the stratospheric polar vortex is corrected and the strength of the polar jet is weakened to be comparable to observation (Charlton-Perez et al 2013). Figure 6 shows the difference of geopotential height at various vertical levels between HT and LT model under goy is based on the data between 1970 and 1999.…”
Section: Discussionmentioning
confidence: 81%
“…In the most recent fifth assessment report (AR5) of the IPCC, 54 models were used for the assessment, among which only half (27) models have full stratosphere with model lid top above 1 hPa. These low-top models have weaker polar vortex variability, and reduced planetary wave activity in stratosphere, leading to much less frequency of major sudden stratospheric warming events in the stratosphere (Charlton-Perez et al 2013;Osprey et al 2013). The Climate-system Historical Forecast Project using 16 coupled models (8 high-top models and 8 low-top models) shows that the high-top models have a more realistic stratospheric response to El Nino and the QBO, and have a possible stratospheric pathway that enhance the wintertime prediction skill over high latitudes and North Atlantic region (Butler et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, general circulation models (including HadGEM2-ES) had been thought to under-estimate the observed posteruption northern hemisphere winter dynamical response (Driscoll et al 2012;Charlton-Perez et al 2013;Bittner et al 2016), but restricting the analysis to the first post-eruption winter and only the strongest volcanic eruptions alters this (Bittner et al 2016;Zambri and Robock 2016). Nevertheless, an improved understanding of the dynamical response to volcanic eruptions is required to clarify the possibility of enhanced winter warming in response to future eruptions.…”
Section: Discussionmentioning
confidence: 99%